A water-soluble glucose-functionalized cobalt(iii) complex as an efficient electrocatalyst for hydrogen evolution under neutral conditions. Issue 4 (10th December 2014) - Yin, Xuguang; Liu, Cuibo; Zhuo, Sifei; Xu, You; Zhang, Bin
Abstract : A water-soluble glucose functionalized cobalt(iii ) complex [Co III (dmgH)2 (py-glucose)Cl] is active and stable for electrocatalytic hydrogen production in neutral aqueous solution. Abstract : A water-soluble glucose-functionalized cobalt(iii ) complex [Co III (dmgH)2 (py-glucose)Cl] is active and stable for electrocatalytic hydrogen production in neutral aqueous solution.